2003
DOI: 10.1046/j.1523-1747.2003.12018.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Expression of μ-Opiate Receptor in Chronic and Acute Wounds and the Effect of β-Endorphin on Transforming Growth Factor β Type II Receptor and Cytokeratin 16 Expression

Abstract: There is evidence that neuropeptides, especially the opiate receptor agonists, are involved in wound healing. We have previously observed that beta-endorphin, the endogenous ligand for the mu-opiate receptor, stimulates the expression of cytokeratin 16 in a dose-dependent manner in human skin organ cultures. Cytokeratin 16 is expressed in hyperproliferative epidermis such as psoriasis and wound healing. Therefore we were interested to study whether epidermal mu-opiate receptor expression is changed at the woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 18 publications
4
53
0
Order By: Relevance
“…β-Endorphin has been reported to exert an anti-inflammatory effect on the skin [38] and to participate in the inhibitory action of UVB-induced melanocyte activation [39]. A previous study found that α-MSH and β-endorphin have opposing biological activities, with α-MSH stimulating adenylate cyclase inducing an increase in cAMP while β-endorphin decreases this α-MSH-generated cAMP accumulation [40].…”
Section: Discussionmentioning
confidence: 99%
“…β-Endorphin has been reported to exert an anti-inflammatory effect on the skin [38] and to participate in the inhibitory action of UVB-induced melanocyte activation [39]. A previous study found that α-MSH and β-endorphin have opposing biological activities, with α-MSH stimulating adenylate cyclase inducing an increase in cAMP while β-endorphin decreases this α-MSH-generated cAMP accumulation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Wound healing (98) Prolactin K8 " Knockout mice lacking the PRL receptor showed decreased expression of keratins K8, K17, K18, and K19 during early pregnancy, accompanied by failure to develop normal mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose of 2 to 8 mg/kg is in the range of effective antinociceptive doses for rats and therefore probably was too high to facilitate angiogenesis. The endogenous MOR and DOR agonist ␤-endorphin was reported to stimulate the expression of cytokeratin 16 (Bigliardi-Qi et al, 2000) and transforming growth factor ␤ type II (Bigliardi et al, 2003) in human skin organ cultures. Both, CK16 and TGF␤ type II receptor are not expressed in normal skin but appear in regenerating epithelial cells of the epidermis during wound healing.…”
Section: Subanalgesic Morphine To Accelerate Healing Processesmentioning
confidence: 99%